Proceedings of the 43nd Annual Upper Midwest Neuro-Ophthalmology Group Meeting, July 23, 2021 and Second Virtual Upper Midwest Neuro-Ophthalmology Group Meeting. (2nd November 2021) - Tajfirouz, Deena; Judge, Casey; Chen, John J.; McClelland, Collin
ABSTRACT: The 43rd meeting of the Upper Midwest Neuro-Ophthalmology Group (UMNOG) took place on July 23, 2021. For the second sequential year, the meeting was held virtually due to the COVID-19 pandemic. The meeting was held in the honour of the late Ivy Dreizin MD. Ninety people attended virtually marking the highest UMNOG meeting attendance on record. There were 23 podium presentations interspersed with numerous personal testimonials recognising Dr Dreizin and her immense contributions to the UMNOG community.